The effect of selenium (Se) on development and nitric oxide levels in Arabidopsis thaliana seedlings - Lehotai, Nóra (Acta Biologica Szegediensis, 2011)
Selenium (Se) is an essential element for many organisms, but its excess leads to toxicity symptoms such as growth inhibition or chlorosis. Since nitric oxide (NO) is a multifunctional signal molecule in plants acting during several physiological plant responses, we examined the effect of selenite treatment on nitric oxide status of Arabidopsis plants during their growth. The effect of selenite on the development and cell viability of seedlings proved to be concentration and time-dependent and it can be explained by the disturbance of protein synthesis, structure and function. Selenite treatment modified the endogenous NO status in the root and the cotyledon of Arabidopsis plants. During the first days after germination the effect of Se was shown to be rather inhibitory on NO content, while during the late developmentin Se-treated plants NO levels increased, which may contribute to growth inhibition.